Essentials of food science - Vaclavik, Vickie A. (Food Science Text Series, 2014)
The fourth edition of this classic text continues to use a multidisciplinary approach to expose the non-major food science student to the physical and chemical composition of foods. Additionally, food preparation and processing, food safety, food chemistry, and food technology applications are discussed in this single source of information. A new section entitled Aspects of Food Processing covers information on Food Preservation, Food Additives, and Food Packaging. Food Safety and Government Regulation of the Food Supply and Labeling are also discussed in this text. As appropriate, each chapter discusses the nutritive value and safety issues of the highlighted commodity. The USDA My Plate is utilized throughout the chapters. A Conclusion, Glossary and further References as well as Bibliography are included in each chapter. Appendices at the end of the book include a variety of current topics such as Biotechnology, Functional Foods, Nutraceuticals, Phytochemicals, Medical Foods, USDA Choosemyplate.gov, Food Label Health Claims, Research Chefs Association certification, Human Nutrigenomics and New Product Development. About the Authors V. A. Vaclavik, Ph.D., R.D., Dr. Vaclavik has taught classes in nutrition, food science and management, and culinary arts for over 25 years at the college level in Dallas, Texas. She is a graduate of Cornell University, human nutrition and food; Purdue University, restaurant, hotel, institution management; and Texas Woman's University, institution management and food science. Elizabeth Christian, Ph.D., has been an adjunct faculty member at Texas Woman's University for 22 years, teaching both face-to-face and online classes in the Nutrition and Food Science department. She obtained her B.S. and her Ph.D. in Food Science from Leeds University, England, and then worked as a research scientist at the Hannah Dairy Research Institute in Scotland for five years before moving to the United States.